2020
DOI: 10.1097/ajp.0000000000000848
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Sleep Disturbance, Pain Catastrophizing, and Pain Intensity for Methadone-maintained Patients With Opioid Use Disorder and Chronic Pain

Abstract: Objective: This study examined the cross-sectional associations among pain intensity, pain catastrophizing, and sleep disturbance among patients receiving methadone maintenance treatment (MMT) for opioid use disorder (OUD) and reporting co-occurring chronic pain. Materials and Methods: Participants were 89 individuals with OUD and chronic pain drawn from a larger cross-sectional study of 164 MMT patients who completed a battery of self-report measures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Cross‐sectionally, we observed a higher prevalence of both knee pain and catastrophizing at baseline among knee OA patients with worse sleep disturbance in a dose‐response manner. This is consistent with existing evidence showing a role of sleep disturbance in pain and catastrophizing (10–13). We found no statistically significant interactions between sleep disturbance and knee pain or catastrophizing when the presence of catastrophizing and knee pain were the outcome measures, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cross‐sectionally, we observed a higher prevalence of both knee pain and catastrophizing at baseline among knee OA patients with worse sleep disturbance in a dose‐response manner. This is consistent with existing evidence showing a role of sleep disturbance in pain and catastrophizing (10–13). We found no statistically significant interactions between sleep disturbance and knee pain or catastrophizing when the presence of catastrophizing and knee pain were the outcome measures, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Yining Wang, BM, Xiaoxi Li, BM, Youyou Zhang, BM, Yubo Ma, MMed, Faming Pan, PhD, Guoqi Cai, PhD: Anhui Medical University and Inflammation and Immune Mediated Diseases Laboratory of Anhui Province, Hefei, China; 2 underlying pathways, are to be clarified. Several cross-sectional studies have confirmed that catastrophizing or pain were more likely to occur in patients with sleep disturbances (10)(11)(12)(13). Interestingly, Tighe et al suggested that pain catastrophizing mediated the association between sleep disturbance and OA symptom severity (14), and Wilt et al showed that pain mediated the relationship between sleep disturbance and pain catastrophizing (15).…”
Section: Introductionmentioning
confidence: 99%
“…A biopsychosocial model of chronic pain has been widely adopted, and epidemiologic studies suggested that chronic pain increases the risk for depression, anxiety, and pain catastrophizing [ 20 , 21 ]. The coexistence of chronic pain and emotional disorders initiates vicious pain, which spirals and amplifies depression and pain catastrophizing and then disturbs daily activities and consequently further exacerbates pain [ 32 34 ]. Depression is a leading cause of disability globally.…”
Section: Discussionmentioning
confidence: 99%
“…It is a risk factor for work disability, and has been linked using the Pain Catastrophizing Scale (PCS) with sleep disturbances. 18,49,50 Perceived injustice, a related factor, has also been identified as a psychological risk factor for delayed recovery following injury. 35 Situations in which individuals consider themselves to have suffered undeserved losses or hardship may lead to perceptions of injustice.…”
Section: Discussionmentioning
confidence: 99%